Not all gut cellular circadian oscillators are food entrainable - Isabel Magaña; S. K. Tahajjul Taufique; Yongli Shan; Melody Shen; David E. Ehichioya; Joseph S. Takahashi; Shin Yamazaki; Yuuki Obata (Proceedings of the National Academy of Sciences, 2026)
Circadian rhythms are ubiquitous, and most of the organs in the body contain circadian oscillators. The intestine comprises diverse cell types with distinct developmental origins and physiological functions. However, which intestinal cells contain cell-autonomous circadian oscillators and how circadian oscillators in distinct intestinal cell types synchronize with one another and with environmental daily cycles remain poorly understood. To address these questions, we generated a Cre-dependent PER2::LUCIFERASE reporter knock-in mouse that enables ex vivo measurement of circadian oscillations in defined cell populations. Ex vivo gut explants from mice expressing the reporter in one of five major cell types of the muscularis externa—enteric neurons (ENs), enteric glial cells (EGCs), interstitial cells of Cajal (ICCs), smooth muscle cells (SMCs), and muscularis macrophages (MMs)—exhibited robust, self-sustained circadian bioluminescence rhythms, demonstrating that each of these cell types harbors a cell-autonomous circadian oscillator. Importantly, circadian oscillators in ENs, EGCs, SMCs, and MMs entrained to feeding-fasting cycles, whereas circadian oscillators in ICCs remained resistant to food entrainment. These findings reveal that distinct intestinal cell types possess unique entrainment properties, and feeding during inactive time induces heterogeneous phase shifts across gut circadian oscillators, leading to temporal circadian misalignment within the intestine. As circadian disruptions, such as those associated with shift work, contribute to intestinal disorders, including inflammatory bowel disease and disorders of the gut–brain interaction, studying how intercellular circadian desynchrony influences intestinal homeostasis should provide chronobiology-based therapeutic strategies to combat these diseases.